2006
DOI: 10.1590/s0100-879x2006001100001
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst-endometrium interaction: intertwining a cytokine network

Abstract: The successful implantation of the blastocyst depends on adequate interactions between the embryo and the uterus. The development of the embryo begins with the fertilized ovum, a single totipotent cell which undergoes mitosis and gives rise to a multicellular structure named blastocyst. At the same time, increasing concentrations of ovarian steroid hormones initiate a complex signaling cascade that stimulates the differentiation of endometrial stromal cells to decidual cells, preparing the uterus to lodge the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Studies in humans and in other mammals have shown that cytokines and growth factors are produced by the pre-implantation embryo and cells of the reproductive tract, even if the exact combinations required for successful implantation are not yet fully understood [23]. Based on the current knowledge of the regenerative effect of PC due to its high growth factor and cytokine content [22], this study proposes a novel therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and in other mammals have shown that cytokines and growth factors are produced by the pre-implantation embryo and cells of the reproductive tract, even if the exact combinations required for successful implantation are not yet fully understood [23]. Based on the current knowledge of the regenerative effect of PC due to its high growth factor and cytokine content [22], this study proposes a novel therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the uterine administration of PC may be useful in peri-implantation, or in the healing process of clinically silent endometrial injuries because many cytokines act as intermediary links in the materno-fetal relationship including decidualization (in the women), implantation, placentation, embryogenesis and fetal growth [23]. Moreover, since pro-inflammatory factor transcripts in bovine endometrial epithelial cells are elevated in case of subclinical or clinical endometritis [24], we hypothesized that an early administration of PC, after artificial insemination (AI) and before the descent of the blastocyst in the uterus, could improve the uterine microenvironment for embryo implantation and counteract eventual subclinical endometritis.…”
Section: Introductionmentioning
confidence: 99%
“…Repeat-breeding cows (animals that after three or more inseminations do not get pregnant because of fertilization failure or early embryonic death) show abnormalities in the growth factor-cytokine network, specifically in endometrial epidermal growth factor (EGF) concentration [12]. The EGF family acts on the trophectoderm, promoting cell attachment and embryo development [13], and its impairment could explain the pregnancy failure in these animals.…”
Section: Introductionmentioning
confidence: 99%
“…A successful pregnancy requires normal embryo implantation and placentation. In this complex developmental process, the proliferation of trophoblast cells is one of the critical events [21][22][23][24][25][26][27] .…”
Section: Functional Categorization By Kegg Pathway and Gene Ontology mentioning
confidence: 99%
“…Scatter plot analysis was made by Microsoft Excel 2000 (Microsoft, USA). Significance Analysis of Microarray (SAM) was performed for the selection of the genes with significant gene expression changes 25 . The statistical significant differentially expressed genes were assessed by computing a q-value for each gene.…”
Section: Microarray Data Analysis and Functional Analysismentioning
confidence: 99%